Identification of dominant-negative mutants of the herpes simplex virus type 1 immediate-early protein ICP0. - Weber, P C (1992)
ICP0 is a 110,000-molecular-weight immediate-early protein of herpes simplex virus type 1 (HSV-1) which is encoded by three exons. It has been shown to function as a promiscuous transactivator of a variety of different HSV-1 and non-HSV-1 promoters in transient expression assays. Analysis of mutations which truncated the carboxy-terminal end of this 775-amino-acid (aa) protein demonstrated that a polypeptide which contained only aa 1 to 553 still possessed significant transactivation potential. Additional carboxy-terminal truncations which sequentially removed aa 245 to 553 and thus the remainder of the third exon resulted in the eventual loss of transactivation capability in these mutants. However, further analysis of these truncated derivatives demonstrated that they behaved as dominant-negative mutants to the wild-type polypeptide. Moreover, one of the mutants was found to act as a promiscuous repressor, in that it could dramatically inhibit a variety of HSV-1 promoters, non-HSV-1 promoters, and heterologous transactivator proteins in transient expression assays, despite having lost almost the entire third exon. These results indicate that a domain encoded by the first two exons probably interacts with, and can effectively titrate, the unknown cellular factor(s) through which ICP0 mediates transactivation.